Multigene phylogeny reveals convergent evolution in small interstitial catfishes from the Amazon and Atlantic forests (Siluriformes: Trichomycteridae). (3rd January 2020) - Costa, Wilson J. E. M.; Henschel, Elisabeth; Katz, Axel M.
Abstract: Interstitial trichomycterid catfishes of the Glanapteryginae and Sarcoglanidinae with uncommon morphology have been known for long time from taxa endemic to the Amazon. In most recent decades, two genera, Listrura and Microcambeva, respectively, placed in Glanapteryginae and Sarcoglanidinae on the basis of morphological characters, have been described from the Atlantic Forest of eastern South America, about 1, 500 km from the area inhabited by those Amazon taxa. Herein, we first test the phylogenetic positioning of Listrura and Microcambeva using a multigene data set, including two nuclear and three mitochondrial genes for nine species of Listrura and Microcambeva and 11 species representing all closely related subfamilies (TSVSG‐clade), as well as five used as outgroups. The phylogenetic analyses generated a robust tree with high support values in all nodes, where monophyly of Glanapteryginae and Sarcoglanidinae is refuted. In contrast, Listrura and Microcambeva form a highly supported clade, herein formally described as a new subfamily, sister to a clade containing taxa representing the Glanapteryginae, Sarcoglanidinae, Stegophilinae, Tridentinae and Vandelliinae. This study also indicates that Microcambeva and Listrura exhibit divergent evolutionary trends in ecological and morphological attributes. Species of Microcambeva inhabit patches of loose sand and possess morphological traits that were convergently acquired by Amazon sand‐dwelling sarcoglanidines, including loss of body pigmentation and long maxilla. Species of Listrura live burrowed inside small stretches of dense leaf litter and have morphological traits that were convergently acquired by Amazon glanapterygines inhabiting leaf litter bottom rivers, including elongate body, with numerous vertebrae and loss or reduction of all fins.